Variations in cervico-vaginal microbiota among HPV-positive and HPV-negative asymptomatic women in Peru - Carrillo-Ng, Hugo (2021)
Objective: To characterize the cervicovaginal microbiota of HPV-positive and HPV-negative asymptomatic Peruvian women, by identifying the presence of 13 representative bacteria genus. Results: A total of 100 HPV-positive and 100 HPV-negative women were matched by age for comparison of microbiota. The following bacteria were more frequently identified in HPV-positive patients compared to HPV-negative: Eubacterium (68 vs 32%), Actinobacteria (46 vs 33%), Fusobacterium (11 vs 6%) and Bacteroides (20 vs 13%). A comparison between high-risk and low-risk genotypes was performed and differences were found in the detection of Actinobacteria (50 vs 33.33%), Bifidobacterium (50 vs 20.83%) and Enterococcus (50 vs 29.17%).